La pandémie de COVID-19, événement planétaire - Éric Triquet (Communication)
For specialists in the social sciences, an event describes primarily a phenomenon experienced as a disruption by a group or more broadly a society. The author presents in this article an analysis of the journalistic treatment of the “COVID-19 pandemic” event by the daily Le Monde. He looks at the media construction of the event through the lens of various levels of information treatment. Articles were collected from the paper’s online archives through subscriber-only keyword searches. The period under consideration is that of the first lockdown in France, from March 17 to May 11, 2020.